The Green Sea Turtle of Guanacaste is Threatened to Extinction by Human Practices - Blanco, Gabriela (2011)
The objective of this study was to analyze the human impacts threatening with extinction the east Pacific green turtle or black turtle (Chelonia mydas). We surveyed the beaches of the northern coast of Guanacaste to observe the presence of nests of this species and to register human threats. At the same time we collected information on beaches where research projects were carried out. The main nesting beaches for east Pacific green turtles were Nombre de Jesús, Zapotillal, Blanca, Matapalo, Prieta y Cabuyal. The main threats were: illegal egg poaching, beach development and uncontrolled tourism. Costa Rica hosts the second larger rockery of east Pacific green turtles and the most important nesting beaches lack of protection. Increase control on these beaches and in its neighboring waters is essential to save this population from extinction.